Evidence against an increase in capillary permeability in subjects exposed to high altitude - Kleger, Gian-Reto; Bärtsch, Peter; Vock, Peter; Heilig, Bernhard; Roberts, L. Jackson; Ballmer, Peter E. (Journal of applied physiology, 1996)
Kleger, Gian-Reto, Peter Bärtsch, Peter Vock, Bernhard Heilig, L. Jackson Roberts II, and Peter E. Ballmer. Evidence against an increase in capillary permeability in subjects exposed to high altitude. J. Appl. Physiol.81(5): 1917-1923, 1996.—A potential pathogenetic cofactor for the development of acute mountain sickness and high-altitude pulmonary edema is an increase in capillary permeability, which could occur as a result of an inflammatory reaction and/or free radical-mediated injury to the lung. We measured the systemic albumin escape by intravenously injecting 5 μCi of125I-labeled albumin and the plasma concentrations of cytokines, F2-isoprostanes (products of lipid peroxidation), and acute-phase proteins in 24 subjects exposed to 4,559 m. Ten subjects developed acute mountain sickness, and four subjects developed high-altitude pulmonary edema. The transcapillary escape rate of albumin was 6.9 ± 2.0%/h (SD) at low (550 m) and 6.3 ± 1.9%/h at high (4,559 m) altitude (P= 0.23; n = 24). The subjects with high-altitude pulmonary edema had a modest but insignificant increase in the transcapillary escape rate of albumin (4.6 ± 1.9%/h at low vs. 5.7 ± 1.9%/h at high altitude;P = 0.42;n = 4). Plasma concentrations of fibrinogen, α1-acid glycoprotein, C-reactive protein, and interleukin-6 were unchanged in the early phases and significantly increased by the end of the observation period in the subjects with high-altitude pulmonary edema, whereas tumor necrosis factor-α and F2-isoprostanes did not change at all. This suggests that the inflammatory reaction was rather a consequence than a causative factor of high-altitude pulmonary edema. In summary, these data argue against a dominant role for increased systemic capillary permeability in the development of acute mountain sickness and high-altitude pulmonary edema.
Gesehen am 17.01.2024